Learning Is [Like] an Act of Writing: The Writerly Turn in Teaching and Learning in Higher Education - Gray, Robert (Teaching and Learning Inquiry, 2025)
Scholarly inquiry into teaching and learning in higher education has long been undertaken through a wide array of theoretical and methodological approaches. This article offers a novel theoretical framework for reconceptualizing and analyzing teaching and learning processes as textual acts. Drawing on Roland Barthes’s concept of the writerly text, this framework enables us to rethink how students engage with course content through positioning learning as an act of meaning making. It also offers insights into how instructors can prompt more meaningful interaction and engagement. For Barthes, writerly texts are texts where the act of reading is an act of re-writing, where the reader is an active participant in producing the text’s meaning. This article applies this writerly conceptual lens to the teaching and learning process in a university STEM course, exploring how positioning the teacher as the author, the course as the text, and the student as the reader might create a space where the student is not just the audience (Barthes 1974, 4) of a course’s content, but also a co-creator.